Toxicological and Pharmacological Activities of Leptohyptis macrostachys (Benth.) Harley and J.F.B.Pastore (Lamiaceae) on Intestinal Smooth Muscle - de Souza, Iara Leão Luna; de Vasconcelos, Maria Allynne; da Silva, Anne Dayse Soares; Silva, Polyana Cristina Barros; Veloso, Carlos Arthur Gouveia; de Araújo, Diego Igor Alves Fernandes; Costa, Vicente Carlos de Oliveira; Pessôa, Hilzeth Luna Freire; Tavares, Josean Fechine; da Silva, Marcelo Sobral; da Silva, Bagnólia Araújo; Cavalcante, Fabiana de Andrade (Frontiers in Pharmacology, 2020)
Leptohyptis macrostachys, previously known as Hyptis macrostachys Benth., is used in folk medicine to relieve the symptoms of asthma, cough and bronchitis. Recently, we showed that the ethanol extract obtained from Leptohyptis macrostachys has selective spasmolytic activity on guinea pig ileum. Therefore, the aim of this study was to characterize the spasmolytic mechanism of this extract, investigated whether it presents toxicological and antidiarrheal activities. Therefore, the crude ethanolic extract of Leptohyptis macrostachys was analyzed by high-performance liquid chromatographic-diode array detection (HPLC DAD). The spasmolytic effect was evaluated on guinea pig ileum, toxicological activity using rats and antidiarrheal activity using male and female mice. In HPLC-DAD analysis, Rosmarinic acid (5.44%) was the most abundant phenolic compound, being considered as a chemical marker. The spasmolytic potency of the extract on histamine-induced contraction was reduced in the presence of 1 mM TEA+, a selective big conductance K+ channels blocker (BKCa). The extract produces a dose dependent antidiarrheal activity, inhibiting equipotently defecation frequency and liquid stool formation. In addition, the extract has inhibited in a dose dependent manner both castor oil induced intestinal transit and intestinal fluid content. Thus, the spasmolytic activity of the extract involves positive modulation of BKCa and its antidiarrheal activity is related to inhibition of intestinal motility and secretion.